An Introduction to Economic Psychology: Areas, Theories and Challenges - Rodríguez, Luis (2021)
The purpose of this paper is to review economic psychology as an interdis-ciplinary area, in which economics and psychology converge. The economic behaviour as its object of study is outlined, as well as the disciplinary characteristics and levels of scientific explanation. In addition, a brief historical overview of the main figures who significantly contributed to its development is presented. On the other hand, some of the theoretical proposals that have the greatest boom in the area are described,some already known such as the theory of planned behaviour, or the theory of the two systems, as well as other new ones, among them financial socialization or the paradigm of life courses are included. Subsequently, the relationship that they could have with areas such as marketing and public policy is established, as well as the differences with behavioural economics. Finally, a series of challenges and recommendations for research in economic psychology today is established as a conclusion.